Hip-Hop Japan : Rap and the Paths of Cultural Globalization - Condry, Ian (Book collections on Project MUSE., 2006)
"In this ethnography Ian Condry interprets Japan's vibrant hip-hop scene, explaining how a music and culture that originated halfway around the world is appropriated and remade in Tokyo clubs and recording studios. Illuminating different aspects of Japanese hip-hop, Condry chronicles how self-described "yellow B-Boys" express their devotion to "black culture," how they combine the figure of the samurai with American rapping techniques and gangsta imagery, and how underground artists compete with pop icons to define "real" Japanese hip-hop. He discusses how rappers manipulate the Japanese language to achieve rhyme and rhythmic flow and how Japan's female rappers struggle to find a place in a male-dominated genre. Condry pays particular attention to the messages of emcees, considering how their raps take on subjects including Japan's education system, its sex industry, teenage bullying victims turned schoolyard murderers, and even America's handling of the war on terror."--Jacket